Islam, economic rationalism and accounting - Sulaiman, Maliah; Willet, R. (International Institute of Islamic Thought, 2001)
This paper discusses the impact ofWestern accounting technologies on belief structures such as those of the Islamic faith. It assesses a theory of accounting and reporting proposed by Baydoun and Willett (1994& 2000). It goes on to consider the nature and origins ofWestern materialist philosophy and contrasts the belief structure of Islam with the West. The paper also examines the historical context in which Western values became adopted inMuslimsocieties and discusses the policy issues that confront Islamic accounting standard setters.